Ecosystem of learning with "augmented reality": educational possibilities - Julio Cabero Almenara; Julio Barroso Osuna (Centro de Estudios Financieros, 2016)
When we speak about «augmented reality» (AR), we can say that we are in front of an emergent technology that is acquiring a great impulse in the educational area. The technology of the AR offers us different possibilities to move to contexts of formation out of the traditional scenes of the formation, to interact real time with the reality, to visualize not perceptible phenomena, to compare an object or phenomenon from different perspectives. These aspects are doing that in the last four years the number of published article in the field of the education has increased progressively. But from our point of view when we refer to his penetration in the educational area, if we do not think about the models and educational paradigms and educational and psychological theories that must give coverage, as well as the role that the teachers and student must play with the same ones, we can see it has happened with other technologies that presented as the future and did not come to the present. They are on these aspects about which we want to think in the present article.